Vibration synergistically enhances IL-1β and TNF-α in compressed human periodontal ligament cells in the frequency-dependent manner - Sutiwa Benjakul; Boontarika Unat; Peungchaleoy Thammanichanon; Chidchanok Leethanakul (Journal of Oral Biology and Craniofacial Research)
Objectives: To investigate whether mechanical vibration at 30 or 60 Hz combined with compressive force alter IL-1β and TNF-α expression in human periodontal ligament (hPDL) cells. Methods: hPDL cells isolated from the roots of first premolar teeth extracted from four independent donors were cultured and exposed to vibration (0.3 g, 20 min per cycle, every 24 h for 3 cycles) at 30 or 60 Hz (V30 or V60), 2.0 g/cm2 compressive force for 2 days (CF), or a combination of compressive force and vibration at 30 Hz or 60 Hz (V30CF or V60CF). Quantitative real-time polymerase chain reaction (qPCR) and enzyme-linked immunosorbent assays (ELISAs) were used to determine IL-1β and TNF-α mRNA and protein, respectively. Results: The levels of IL-1β and TNF-α did not alter in groups V30 and V60. While, they were upregulated in groups CF, V30CF and V60CF. In addition, IL-1β mRNA and TNF-α mRNA and protein were expressed at significantly higher levels in group V30CF compared to CF group. However, IL-1β protein levels between V30CF and CF groups did not reach statistical significance. Conclusions: 30 Hz vibration had the synergistic effects with compressive force on the upregulation of IL-1β mRNA and TNF-α mRNA and protein in PDL cells, while 60 Hz vibration did not have this synergistic effect.